STUDY OF THE EFFECT OF MINERAL ADMIXTURE ADDITION ON PAVING BLOCKS' PHYSICAL AND MECHANICAL PROPERTIES - lo, Hansen; Sutandar, Erwin; Budi, Gatot Setya (Jurnal Teknik Sipil, 2024)
Paving blocks, concrete bricks made from cement and sand, are a vital alternative to ground cover. Their extensive, precast nature, water absorption capabilities, affordability, and ease of use contribute to their popularity. However, the additional ingredients, particularly mineral admixtures, hold the potential to enhance these blocks' quality and performance significantly. The mineral admixtures used, such as limestone, quartz sand, and gypsum, are instrumental in improving the performance of paving blocks, offering a promising avenue for further research and application. This research, conducted with meticulous scientific rigor, investigated paving blocks' physical and mechanical properties. Paving block test objects were created using sand, cement, and crushed stone with mineral admixtures. The mineral admixtures used in this experiment, including gypsum, quartz sand, and limestone, were crushed before being used in a stone cruiser machine to make them powder and reactive. Compressive strength test, weat resistance test, volume weight test, water absorption test, and visual inspection were conducted experimentally. The research results, derived from a robust experimental setup, revealed that paving blocks with 10% gypsum additives, 6% quartz sand powder, and limestone powder produced a more excellent compressive strength value than standard paving blocks, values of 36,884 MPa, 37,573 MPa, and 38,950 MPa with a regular paving block compressive strength value of 36,119 MPa followed by a decrease in the percentage of absorption. This suggests that using mineral admixtures at a certain percentage as an additional material can improve the quality of paving blocks. However, it is essential to note that adding too many mineral admixtures can also decrease the strength of the paving block, emphasizing the need for careful application of these materials in construction. These findings provide valuable insights for civil engineers, construction professionals, and researchers in materials science and construction technology, enhancing their understanding of the role of mineral admixtures in paving block strength.